Mobility Coupled with Motivation Promotes Survival: The Evolution of Cognition as an Adaptive Strategy - Stefano, George B; Kream, Richard M; Esch, Tobias (Biology, 2023)
Morphine plays a critical regulatory role in both simple and complex plant species. Dopamine is a critical chemical intermediate in the morphine biosynthetic pathway and may have served as a primordial agonist in developing catecholamine signaling pathways. While dopamine remains the preeminent catecholamine in invertebrate neural systems, epinephrine is the major product of catecholamine synthetic pathways in vertebrate species. Given that the enzymatic steps leading to the generation of morphine are similar to those constraining the evolutionary adaptation of the biosynthesis of catecholamines, we hypothesize that the emergence of these more advanced signaling pathways was based on conservation and selective "retrofitting" of pre-existing enzyme activities. This is consistent with observations that support the recruitment of enzymatically synthesized tetrahydrobiopterin (BH4), which is a cofactor for tyrosine hydroxylase, the enzyme responsible for dopamine production. BH4 is also an electron donor involved in the production of nitric oxide (NO). The links that coordinate BH4-mediated NO and catecholaminergic-mediated processes provide these systems with the capacity to regulate numerous downstream signaling pathways. We hypothesize that the evolution of catecholamine signaling pathways in animal species depends on the acquisition of a mobile lifestyle and motivationally driven feeding, sexual, and self-protective responses.